2022
DOI: 10.3389/fpsyt.2022.922788
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative and quantitative study of self-reported positive characteristics of individuals with ADHD

Abstract: Research in Attention-deficit/hyperactivity disorder (ADHD) has had a clear focus on treatment and the dysfunction in specific situation associated with the condition. However, self-report, observational and anecdotal evidence indicates that there are also positive aspects associated with ADHD. Research on the potential positive features in individuals with an ADHD diagnosis is still limited, especially studies with larger representative samples. Here we performed qualitative research to identify positive aspe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
2
13
1
Order By: Relevance
“…Career coaching has an extensive history of promoting a strength perspective. Schippers et al (2022) note that strengths can have positive or negative consequences depending on context. Pauwels (2015) cautioned that some of the most meaningfully positive life experiences are frequently inspired by negative circumstances and thus over-focus on the positive may be counterproductive.…”
Section: A Strength Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…Career coaching has an extensive history of promoting a strength perspective. Schippers et al (2022) note that strengths can have positive or negative consequences depending on context. Pauwels (2015) cautioned that some of the most meaningfully positive life experiences are frequently inspired by negative circumstances and thus over-focus on the positive may be counterproductive.…”
Section: A Strength Focusmentioning
confidence: 99%
“…Career coaching has an extensive history of promoting a strength perspective. Schippers et al. (2022) note that strengths can have positive or negative consequences depending on context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] However, these studies have largely included small samples of high-functioning adults with ADHD. One exception is the study by Schippers et al, 26 which applied both qualitative and quantitative methods to examine perceived positive characteristics with ADHD in a large sample of 206 adults with ADHD. 26 Almost all of the participants in the study reported positive aspects related to ADHD, with core themes being creativity, being dynamic, flexibility, socioaffective skills and higher order cognitive skills.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…This is fuelled, among others, by the realization that a minority of people with ADHD thrive and are, for example, successful entrepreneurs, comedians, or inventors (Hoogman, Stolte, Baas, & Kroesbergen, 2020). This suggests that ADHD is associated with positive traits and assets under some circumstances, which is indeed confirmed by many people with ADHD (Schippers et al, 2022). This positive side of ADHD, and protective factors that promote a positive life trajectory, have been largely understudied and left unexploited for treatment, prevention, or health promotion.…”
mentioning
confidence: 97%